Methyl-substitution of an iminohydantoin spiropiperidine β-secretase (BACE-1) inhibitor has a profound effect on its potency. Issue 21 (1st November 2015) - Egbertson, Melissa; McGaughey, Georgia B.; Pitzenberger, Steven M.; Stauffer, Shaun R.; Coburn, Craig A.; Stachel, Shawn J.; Yang, Wenjin; Barrow, James C.; Neilson, Lou Anne; McWherter, Melody; Perlow, Debra; Fahr, Bruce; et al.
Graphical abstract